2014
DOI: 10.1002/pc.23068
|View full text |Cite
|
Sign up to set email alerts
|

The structure and photocatalytic performances of mechanically synthesized poly(3′,4′‐ethylenedioxy‐2,2′:5′,2″‐Terthiophene)/Zno composites

Abstract: Poly(3 0 ,4 0 -ethylenedioxy-2,2 0 :5 0 ,2 00 -terthiophene)/ZnO(poly(TET)/ZnO) composites with the ratio of poly(TET) and nano-ZnO from 3:1 to 1:3 were synthesized by hand grinding and ball milling methods, respectively. The photocatalytic activities of the composites were examined through the degradation processes of methylene blue (MB) solution under UV light irradiation, and the possible mechanism for the photocatalytic activity enhancement by synergetic effects between nano-ZnO and poly(TET) was proposed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…26,29 The intensely strong peak at 785 cm −1 , as well as a weaker characteristic peak at 832 cm −1 , indicated that the TTh monomer was successfully polymerized and the coupling reactions occurred at the C α , C α′ positions. 27,30,31 As shown in Fig. 1a, a blood-orange fluffy layer formed on the GP, and the color of the layer gradually changed from orange-yellow to orange-brown when increasing the number of electrodeposition cycles and thereby increasing the layer thickness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…26,29 The intensely strong peak at 785 cm −1 , as well as a weaker characteristic peak at 832 cm −1 , indicated that the TTh monomer was successfully polymerized and the coupling reactions occurred at the C α , C α′ positions. 27,30,31 As shown in Fig. 1a, a blood-orange fluffy layer formed on the GP, and the color of the layer gradually changed from orange-yellow to orange-brown when increasing the number of electrodeposition cycles and thereby increasing the layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks of the aromatic ring-stretching vibrations appeared at 1352, 1425, 1440 and 1492 cm −1 . [25][26][27] Vibrations at 922 and 686 cm −1 originated from the stretching of the C-S bond in the thiophene ring. 27,28 The peaks observed at 3062 and 1069 cm −1 corresponded to the stretching vibration and inplane bending vibration of C β -H in the thiophene ring, respectively.…”
Section: Ptth Electrode Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the accessibility and simplicity of catalytic materials, photocatalytic degradation has garnered considerable interest. [35][36][37][38][39] The extensively used nano-catalysts are Cu, 40,41 CdS, 42,43 ZnO, 44,45 32,[51][52][53][54] or its composites. 55 Compared to other polymetric semiconductor photocatalysts, graphitic carbon nitride (g-C 3 N 4 ) has the highest band gap of 2.7 eV, which works under visible light to degrade organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the accessibility and simplicity of catalytic materials, photocatalytic degradation has garnered considerable interest 35–39 . The extensively used nano‐catalysts are Cu, 40,41 CdS, 42,43 ZnO, 44,45 TiO 2, 33,46–48 SnO 2, 49 and ZrO 2, 50 polymer‐based catalyst 32,51–54 or its composites 55 …”
Section: Introductionmentioning
confidence: 99%